2014
DOI: 10.1002/pssb.201451534
|View full text |Cite
|
Sign up to set email alerts
|

Carrier distributions in InGaN/GaN light‐emitting diodes

Abstract: The distribution of carriers in InGaN/GaN quantum well light‐emitting diodes is frequently calculated using drift‐diffusion models. Using this type of approach, it is found that the holes are preferentially captured into the quantum wells closest to the p‐type injection layer. This type of model, however, only deals with the initial capture of carriers into the quantum wells, and not any subsequent redistribution of carriers caused by carrier escape or tunnelling. However, thermally driven carrier redistributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…We model the MQW structure as a single equivalent QW. This is reasonable because carrier transient times between the QWs in a GaN MQW structure have been reported to be in the range of a femtosecond [52,53] in InGaN/ GaN LEDs. This is significantly faster than the characteristic times of the carrier recombination and of the QW escape processes.…”
Section: Dynamic Photon Generation Modelsmentioning
confidence: 53%
“…We model the MQW structure as a single equivalent QW. This is reasonable because carrier transient times between the QWs in a GaN MQW structure have been reported to be in the range of a femtosecond [52,53] in InGaN/ GaN LEDs. This is significantly faster than the characteristic times of the carrier recombination and of the QW escape processes.…”
Section: Dynamic Photon Generation Modelsmentioning
confidence: 53%
“…Thus, the QW number is usually around 10 or even up to 15. Besides, the recent study also indicated that the carrier densities are uniform in different QWs due to the thermally assisted transport [ 94 ]. Thus, it is reasonable to assume a uniform carrier distribution and the deviation between this assumption and the actual situation is not as large as expected.…”
Section: Carrier Lifetime Measurementmentioning
confidence: 99%
“…Green emission can be obtained from InGaN/GaN QWs by increasing the indium fraction, but these devices have significantly reduced efficiency compared to their blue-emitting counterparts, having EQE's of typically 20-50% 1 depending on the specific emission wavelength. There have been several mechanisms suggested for this reduction in efficiency 1,3,4 . The higher indium content needed to get into the green spectral region increases the polarisation fields across the QW, which reduces the electron-hole overlap and thus the rate of radiative recombination.…”
Section: Introductionmentioning
confidence: 99%
“…The higher indium content needed to get into the green spectral region increases the polarisation fields across the QW, which reduces the electron-hole overlap and thus the rate of radiative recombination. Also, the higher indium content is achieved by growing the QW at a lower temperature, resulting in a higher concentration of point defects that act as centres of nonradiative recombination 4 . Thus, overall, nonradiative recombination competes more successfully with radiative recombination in green wz QWs than their blue counterparts.…”
Section: Introductionmentioning
confidence: 99%